Water, sanitation and hygiene (WASH) index for primary healthcare facilities: Towards achieving WASH security - Odjegba, Enovwo E.; Bankole, Abayomi O. [UNESP]; Sadiq, Adebayo; Layi-Adigun, Barakat O.; Adebimpe, Abayomi M.; Kosemani, Mariam O.; Ojo, Emmanuel B.; Adewuyi, Mustapha A. (Elsevier, 2024)
This study focused on designing a WASH Index for assessing the status of WASH in Primary Healthcare Facilities (PHCs) especially for low- and middle-income countries. To assess the effectiveness of the WASH Index in evaluating the WASH in PHCs, PHCs were selected from 70 Local Government Areas (LGA) across 3 Southwestern States in Nigeria. The WASH index comprises of the five Joint Monitoring Programme service ladders as outlined in the World Health Organization Global Baseline Report for monitoring basic WASH services in health care facilities: water, sanitation, hygiene, waste management and environmental cleaning. The 5 service elements (termed as components) assessed were based on 10 indicators and 30 sub-indicators. The results of the WASH Index of the PHCs were compared statistically on LGA and State basis with emphasis on the status of WASH facilities. The study concludes that the result would further provide baseline information on the status of WASH in PHCs in the selected States in the quest to achieve the Sustainable Development Goals (SDGs). This study recommends that the WASH Index could be adopted an assessment tool for evaluating WASH in PHCs in other to ensure communication of results to policy makers and other relevant stakeholders, for effective monitoring healthcare facilities.
Keywords: Indicators; LMICs; Primary healthcare facilities; Service ladders; WASH